Future health expenditure in the BRICS countries: a forecasting analysis for 2035 - Pragyan Monalisa Sahoo; Himanshu Sekhar Rout; Mihajlo Jakovljevic (Journal of Global Health, 2023)
This study examined the health expenditure trend among the BRICS from 2000 to 2019 and made predictions with an emphasis on public, pre-paid, and out-of-pocket expenditures for 2035.
Keywords: Health policy; Health systems; Maternal health; Public health; Child health